Evaluation of marker assisted backcross breeding derived lines for morpho-physiological characters under late sown heat stress condition in bread wheat - Amasiddha, B.; Ramya, K.T.; Kumar, C Prashant; Neha, R.; Leena, T.; krishna, Hari; Ramya, P.; Jain, N.; Singh, P.K.; Singh, G.P.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
An experiment was conducted to study the performance of BC2F3 and BC1F4 lines derived in marker assisted backcross breeding (MABB) program for different morphological and physiological traits under late sown conditions. Two QTLs were introgresed into HD2733, one for days to anthesis and other for yield under stress conditions from an identified heat tolerant variety WH730 (donor). The lines were subjected to heat stress by sowing late in the season and the data was recorded on several characters at different phenological stages. A significant difference (P<0.05) between BC2F3 and BC1F4 lines for many traits at phenotypic level was observed but a few traits did not show significant difference and the lines were more and less similar with recurrent parent HD2733. Backcross derived lines showed improvement over recurrent parent for some important morpho-physiological traits including yield under high temperature stress condition. However, overall performance of BC2F3 lines was slightly better than the BC1F4 lines for morpho-physiologically important characters. For most of the DUS traits, both BC2F3 and BC1F4 lines were having closer values to the recurrent parent attributing to the recovery of the recipient parent genome. Seventeen BC2F3 and 10 BC1F4 lines were selected for their superior performance which will be further evaluated in multilocation trials.